Investigating the Perception of Success in Software Projects Among Developers from a Brazilian Software Company - Nascimento, Cláudio; de Mello, Rafael (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2022.20971, 2022)
Understanding and properly applying agile practices in software development projects is a common challenge for developers. Consequently, the expected benefits of these practices may not be perceived, hampering developers from reaching critical success factors of software projects. This work aims to investigate the perception of success in software projects in the context of a Brazilian software company whose development process is based on Scrum. Besides, the development teams from this company follow several technical and non-technical agile practices. For this purpose, we conducted an opinion survey with 17 developers distributed among four development teams of this company. The survey findings revealed prevailing gaps in the teams' perception of critical success factors in their projects despite following a common subset of agile practices addressing them. Among others, the gaps include a lack of perceiving realistic schedules, clear requirements, and good quality management. Aiming at improving this scenario in the company, we plan to conduct a collaborative action research with one of the development teams investigated.